2015
DOI: 10.1590/s0036-46652015000400018
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Disseminated Cryptococcosis With Renal Involvement in an Hiv-Infected Patient

Abstract: SUMMARYIntroduction: We present a fatal case of disseminated cryptococcosis in a young man whose diagnosis of HIV infection was made at the time of admission to the emergency room. Case report: The patient was a twenty-three-year-old man, with a history of daily fever during one month associated with diarrhea, weight loss, headache, vomiting and generalized seizures. He also had a history of diabetes mellitus, alcoholism and drug addiction. Upon physical examination the patient was pale, disoriented and had pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Interestingly, kidney damage in disease group was observed. As of now limited published data is available on kidney involvement in cryptococossis 36 . Thus the pathophysiology of renal involvement in cryptococcosis needs to be addressed.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, kidney damage in disease group was observed. As of now limited published data is available on kidney involvement in cryptococossis 36 . Thus the pathophysiology of renal involvement in cryptococcosis needs to be addressed.…”
Section: Resultsmentioning
confidence: 99%
“…Aragão et al (2008), described a case of bilateral amaurosis due to cryptococcal meningitis in a patient from Ceará. Daher et al (2015), reported a fatal case of cryptococcosis in a 23-year-old man with HIV and diabetes mellitus. Additional details about these cases were not provided.…”
Section: Cearámentioning
confidence: 99%